Representasi Makna Patriotisme dalam Film Genre Perang - Tzarini Ayuning Bidhuri; Aning Sofyan (UNISBA Press, 2022)
Abstract. In modern times like now, there are lots of entertainment facilities for everyone to enjoy, one of which is film. Films have various types of genres, one of which is war, which of course has the theme of patriotism. Along with the currents of modernization and globalization, of course, the sense of patriotism is not the same as before, there are gaps everywhere. Therefore, it is necessary to have a means that can convey the message of patriotism so that people can understand the meaning of patriotism, one of which is the mass media, namely film. The purpose of this research is to find out the meaning of connotations, denotations and myths contained in the scene of the film